2007
DOI: 10.1057/palgrave.jit.2000102
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Institutional Logics: A National Programme for IT in the Organisational Field of Healthcare

Abstract: This paper reports the findings from a 4-year study on the UK National Health Service on the introduction of a national programme for information technology. 1 This is the largest civil IT programme worldwide at an estimated technical cost of d6.2 billion over a 10-year period. An institutional analysis of our historical and empirical data from six NHS organisations identifies growing fragmentation in the organisational field of healthcare, as past and present institutional logics both fuel and inhibit changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
235
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 28 publications
(22 reference statements)
7
235
1
2
Order By: Relevance
“…In particular, research has considered the tensions between (i) institutional arrangements in one organizational field within which innovation happens; and (ii) the institutional logic embodied within the IT innovation itself. For example, misalignments between institutional arrangements on one hand and a medical innovation (Cho and Mathiassen, 2007;Jensen et al, 2009), or a nationwide IT programme (Currie and Guah, 2007) on the other, were found to explain the lack of adoption within healthcare settings. Similarly, it has been suggested that mismatches between the institutional logic embodied within a new information system and the dominant institutional logic within the adopting organization create resistance to the implementation of IT innovations at an organizational level (Gosain, 2004).…”
Section: Stage Of Adoption Type Of It Innovation (Authors) Intention mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, research has considered the tensions between (i) institutional arrangements in one organizational field within which innovation happens; and (ii) the institutional logic embodied within the IT innovation itself. For example, misalignments between institutional arrangements on one hand and a medical innovation (Cho and Mathiassen, 2007;Jensen et al, 2009), or a nationwide IT programme (Currie and Guah, 2007) on the other, were found to explain the lack of adoption within healthcare settings. Similarly, it has been suggested that mismatches between the institutional logic embodied within a new information system and the dominant institutional logic within the adopting organization create resistance to the implementation of IT innovations at an organizational level (Gosain, 2004).…”
Section: Stage Of Adoption Type Of It Innovation (Authors) Intention mentioning
confidence: 99%
“…There is, however, mounting evidence that organizations are subject to competing institutional demands within their organizational fields (Reay and Hinings, 2009;Scherer et al, 2013), and that these conflicting demands influence IT innovation adoption (Butler, 2003) and diffusion (Currie and Guah, 2007). However, existing information systems research has primarily examined one category of conflictsmisalignments between the organizational field and the institutional demands embodied within the IT artefact (see Gosian, 2004;Jensen et al, 2009) (STREAM 2).…”
Section: Stage Of Adoption Type Of It Innovation (Authors) Intention mentioning
confidence: 99%
See 3 more Smart Citations